Potencial biotecnológico da casca da Mimosa tenuiflora (jurema preta) – biossorção de íons metálicos - Cabral, Anelise Arruda (2020)
Toxic metal ions arouse environmental concerns due to their danger to human health and the environment, mainly due to inadequate treatment and disposal of industrial effluents. Among the treatment methods used, biosorption has been an effective alternative in removing these contaminants, mainly because they use low-cost materials. The objective of this work was to evaluate the potential of Mimosa tenuiflora bark as a bioadsorber for the removal of metal ions such as copper and nickel present in a synthetic effluent. The barks were collected in Fagundes/PB, crushed and washed with distilled water and dried in a circulating oven at 70ºC for 24 hours, the acidic chemical modification was done with hydrochloric acid (0.1 mol L^-1 ) and the basics with hydroxide sodium (0.1 mol L^-1 ). The bioadsorber was characterized by the PCZ, FTIR and SEM techniques. A complete factorial design was carried out 2^5 , having as independent variables: mass of the adsorbent, concentration of the adsorbate (Copper), pH of effluent, contact time and activation of the bark, the effects of these variables were analyzed on the responses: adsorption capacity (q) and percentage of removal of copper ions (%Red). The best results were observed in experiments 23 and 31 (0.2 g bark, concentration 40 mg L^-1 , pH 8, the acid activated bark and differentiating in time, 20 and 40 minutes respectively. In the study of pH influence, the pH of the copper effluent itself (4.8), presented satisfactory results, without the need for adjustments. With the best conditions, kinetic studies, equilibrium isotherms and desorption with acid and basic bark for copper and nickel were performed. The washed, acidic and basic bark had a pHPCZ of 4.4; 3.1 and 6.5 respectively, the SEM showed a more porous surface in activated barks, the FTIR indicated the presence of functional groups such as -OH, -COOH, -COO-, -CO. The pseudo-second order kinetic model adjusted better to the experimental data. The non-linear isotherm Langmuir was the one that best fitted, with maximum experimental adsorption capacity 8.87; 16.93 mg g^-1 of Cu^2+ and 1.64; 9.51 mg g^-1 of Ni^2+ for acid and basic bark respectively, indicating an adsorption process in monolayers, mainly by chemosorption. The activated barks did not show satisfactory results of nickel desorption, as did the basic bark for copper. The copper acid bark showed excellent results in the desorption process, with 3 reuse cycles with efficiency greater than 70%. The results showed a relevant potential of the bio-absorbent from the bark of Mimosa tenuiflora, which was never investigated for this purpose.